2008
DOI: 10.1111/j.1468-0297.2008.02144.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Markets and Exogenous Laboratory Experiments: A Case Study of The Winner's Curse

Abstract: We examine the relevance of experimental findings from laboratory settings that abstract from the field context of the task that theory purports to explain. Using common value auction theory as our guide, we identify naturally occurring settings in which one can test the theory. Experienced agents bidding in familiar roles do not fall prey to the winner's curse. Yet, experienced agents fall prey to the winner's curse when bidding in an unfamiliar role. We conclude that the theory predicts field behaviour well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…However, there is growing evidence that providing a context for the experiment might be desirable, especially in cases when the participants have direct experience with the particular context being studied. For example, both Cooper et al (1999) and Harrison and List (2005) find that introducing a context that expert subject pools recognize 1 The results in Cameron et al (2006) are consistent with the outcome of the surveys conducted by Transparency International in 44 countries which showed that Indonesians were the most optimistic about future corruption reduction while Indians were amongst the most pessimistic. See unpan1.un.org/intradoc/groups/public/documents/APCITY/UNPAN016537.pdf.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, there is growing evidence that providing a context for the experiment might be desirable, especially in cases when the participants have direct experience with the particular context being studied. For example, both Cooper et al (1999) and Harrison and List (2005) find that introducing a context that expert subject pools recognize 1 The results in Cameron et al (2006) are consistent with the outcome of the surveys conducted by Transparency International in 44 countries which showed that Indonesians were the most optimistic about future corruption reduction while Indians were amongst the most pessimistic. See unpan1.un.org/intradoc/groups/public/documents/APCITY/UNPAN016537.pdf.…”
Section: Introductionsupporting
confidence: 86%
“…The literature that has sought to examine subject pool effects has largely explored gender and educational differences amongst students. 4 Recently, there has been an increase in the use of non-standard subject pools in experiments, such as financial market traders (Alevy et al 2006), sportscard dealers (List 2003;Harrison and List 2005), nurses (Cadsby and Maynes 1998;Barr et al 2004), CEOs (Fehr and List 2004), managers in Chinese state-owned enterprises (Cooper et al 1999), public affairs officials (Potters and van Winden 1996), and a random sample of the general population (Carbone 2005). Only a subset of these studies directly compares the results from the non-standard subject pool with the results from the student subject pool.…”
Section: Introductionmentioning
confidence: 99%
“…Similar forms of extrapolation have been documented by experimental economists looking at the links between the lab and the field (Harrison & List, 2004;Levitt & List, 2007a, 2007bLevitt, List, & Reiley, 2010). Successful skills and heuristics evolved in some familiar situations carryover to other similar field or lab settings: for instance, experienced sports-cards dealers did not fall prey to the typical winner's curse in a lab auction (Harrison & List, 2008), whereas professional football players played more equilibrium strategies than students in laboratory coordination games (Palacios-Huerta & Volji, 2008). These rationality crossovers are conceptually close to some of the semantic or procedural priming effects documented in the psychology literature (Forster, Liberman, & Friedman, 2007;Gollwitzer et al, 1990;Kruglanski et al, 2002;Neely, 1977).…”
Section: Promoting Spilloversmentioning
confidence: 98%
“…The second problem is an "experience problem" referring to a claim, see Harrison and List (2003) for an example, that professionals who bid in such auctions regularly do not usually lose money and therefore the experiments tell us little about the field auctions. The claim is based on the idea that unsuccessful bidders leave the market and so only those bidders who do not suffer such biases will remain.…”
Section: Resultsmentioning
confidence: 99%